Genetic characterisation of Echinococcus granulosus sensu lato infecting ruminants in the Republic of North Macedonia L. - Rashikj, L; Stefanovska, J; Djadjovski, I; Popova Hristovska, Z; Xhekaj, B; Trajchovski, A; Chapkunovska, B; Jurhar Pavlova, M; Cvetkovikj, A (Journal of the Hellenic Veterinary Medical Society, 2025)
This study aimed to characterize Echinococcus genotypes infecting ruminants in North Macedonia and estimate their epidemiological significance and possible public health implications. Samples from 69 ruminants were collected between 2021 and 2022, with one cyst per animal analyzed for genetic diversity through amplification and sequencing of the cytochrome c oxidase 1 (cox1) mitochondrial gene. Using the neighbor-joining method, phylogenetic analysis of the sequenced data was performed using MAFFT for sequence alignment, trimming, and tree construction with MEGAX. Phylogenetic analysis identified two major genotypes: G1 and G3. Among the samples, 38/61 sheep (62.3%) were G1, and 23/61 sheep (37.7%) were G3. Both G1 and G3 genotypes were detected in 4/8 isolates (50%) in cattle. This study provides the first molecular characterization of Echinococcus granulosus (s.s.) genotypes (G1 and G3) in North Macedonian ruminants. The predominance of these highly zoonotic genotypes highlights significant public health risks and underscores the urgent need for integrated surveillance programs targeting both animal and human populations. These findings provide essential baseline data for implementing targeted control strategies in this endemic region.